Research on Performance Evaluation and Improvement of Ifraz-2 Water Treatment Plant - Omar, Imad A.; Aziz, Shuokr Q. (Recent Research Advances in Biology Vol. 7, 2021)
Study of performance of water treatment plant (WTP) is essential to be assessed with all aspects and considerations including physical, chemical and bacteriological so as to determine its efficiency and to produce quality water to the consumer. Performance of any WTP is a crucial parameter to be evaluated to understand its operation, working, and efficiency. The present study aimed to evaluate the performance of Ifraz 2 WTP units, and to discover the problems of the efficiency in the units with providing appropriate solutions. Water samples were collected for six months from raw water, after clarification, after filtration, and storage tank. Turbidity removal efficiency for each unit and the whole WTP were calculated and presented. Results revealed that there is a wide variation of the raw water turbidity values which ranged from 51.8 NTU to 1978 NTU. Average removal efficiencies for the sedimentation unit, filtration unit, and the entire Ifraz 2 WTP were 92.25%, 64.99% and 97.54%, respectively. The efficiency of coagulation and flocculation processes are fluctuated due to the absence of optimum dosage of coagulant. In the filtration process, due to the little depth of filter bed, this makes the filtration process in low quality. For improving the process of filtration, an adequate adding of filter media is very necessary to improve filter efficiency. After disinfection and storage, the turbidity values of the treated water were increased in half of the samples due to availability of solids in the storage tank. A great part of solids removed after coagulation-flocculation and sedimentation tanks.